O discurso reportado em manuscritos escolares brasileiros e franceses: um estudo contrastivo a partir do gênero “contos etiológicos” - Amorim, Kariny Louizy Silva (2013)
The reported speech is a fundamental component in children's fictional narratives, fulfilling a representational role of an utterance another in a given utterance (Bakhtin and Voloshinov, 1995). In studies on the production of this type of text written by young scribes in the school, Boré (2009, 2010) points to the importance of dialogue, signaling it as an element capable of acting as an "engine" of the invention, boosting the deployment of storytelling and writing. However, while recognizing the relevance of these investigations conducted by the author, speech development reported in their written statements proves to be a subject still little explored in the context of language acquisition, especially if you look from the perspective of analysis involving the comparison between different languages . Based on these assumptions – they also bring a strong link with the theoretical postulates related to Bakhtin's notions of dialogism and polyphony, and studies in the field of speech reported – developed by Authier-Revuz – and anchored, even in a contribution theoretical and methodological arising Genetics Textbook – from which we conceive of writing as a process – and Enunciation Linguistics, in this work, we are dedicated to investigating the differences and similarities regarding the presence of reported speech found in manuscripts of short stories etiological invented by dyads newly literate students at a school in Brazil and one from France. These manuscripts were collected from the immersion of both groups of students in reading this particular genre – which also known as "origin tale", consists of a fictional narrative that seeks to explain the origin of beings, properties, nature phenomena, etc. (Cascudo, 2006) – and the realization of didactic proposals and similar textual production, made in the classroom of each school in both countries. This expedient gathered more than 80 productions, among which we selected 34 students of French and 37 Brazilians to be analyzed here and, from them, describing the ways in which these students belong, in their texts, this type of discourse, dialogue represented. Our observations suggest, therefore, that such a discursive element is present in more than half the number of manuscripts produced by both the French and the Brazilian students. However, the latter employ it in his tales with a significantly higher frequency than the first. In turn, the reported speech form that predominates in the composition of narratives, both for students and for those of Brazil in France, is the direct discourse (DD), which seems to confirm the hypothesis raised by the theoretical framework assumed in this work, namely: the dialogical structure represented the DD would be reminiscent of dialogic inner speech that would allow these young clerks set up a fictional universe. Thus, we believe it is possible for these students to supplement their storytelling skills.